2021
DOI: 10.29392/001c.24357
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and comparison of the sub-Saharan Africa and original WHO maternal near-miss criteria in a rural hospital in Western Tanzania

Abstract: BackgroundAfter the introduction of the maternal near-miss (MNM) criteria by the World Health Organization (WHO), an adapted version for low-income countries was defined but has never been validated in a rural hospital in this setting. Aim of this study was to identify the occurrence of MNM by both the use of the WHO and the adapted sub-Saharan Africa (SSA) MNM tool and to compare the applicability of both versions. MethodsThis cross-sectional study was done between November 2019 and July 2020 in Ndala Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…The SSA MNM ratio reported here is similar to those reported in Namibia, Tanzania, and Ethiopia 11–13 ; however, it is higher than in studies conducted in Kenya, Nigeria and Suriname 14–17 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The SSA MNM ratio reported here is similar to those reported in Namibia, Tanzania, and Ethiopia 11–13 ; however, it is higher than in studies conducted in Kenya, Nigeria and Suriname 14–17 …”
Section: Discussionsupporting
confidence: 84%
“…The SSA MNM ratio reported here is similar to those reported in Namibia, Tanzania, and Ethiopia 11 , 12 , 13 ; however, it is higher than in studies conducted in Kenya, Nigeria and Suriname. 14 , 15 , 16 , 17 The variation could be the result of differences in study populations or the types of healthcare facilities in which the studies were conducted.…”
Section: Discussionsupporting
confidence: 82%
“…Different studies in SSA countries, including Ethiopia, reported the increment of NNM during the COVID-19 pandemic ( 29 33 ). This could be due to the interruption of essential maternal newborn and child health services which has impacted millions of lives across the world ( 34 ).…”
Section: Introductionmentioning
confidence: 99%